Saving Ukrainian cultural heritage online: a global initiative - Jolicoeur, Kiley; Kijas, Anna; Rakityanskaya, Anna (Ukrainian Cultural Studies, 2022)
Saving Ukrainian Cultural Heritage Online (SUCHO) is a unique global rapid-response initiative focused on safeguarding the digital cultural heritage of Ukraine, which is under threat due to the ongoing Russian invasion. The project unites an international team of 1500 volunteers led by digital humanities specialists and is in partnership with a number of organizations who provide technological and/or financial support for the initiative. The project archives websites and digital collections of Ukrainian cultural institutions, with the intention of being able to provide the originating institutions with access to this web archive in the event of content loss. In addition to web archiving, the project is developing metadata for all of the archived websites and collections, raising funds to procure and distribute emergency digitization equipment to cultural institutions in Ukraine, and facilitating the creation of training materials for that equipment. In order to promote Ukrainian cultural heritage across the globe, SUCHO has launched two curated online galleries: Exploring Ukrainian Cultural Heritage Online and SUCHO Meme Wall.